Assessing Effectiveness of a Nonhuman Animal Welfare Education Program for Primary School Children. Issue 3 (3rd July 2017) - Hawkins, Roxanne D.; Williams, Joanne M.; ,
ABSTRACT: Nonhuman animal welfare education aims to promote positive relationships between children and animals and thus improve animal welfare, yet few scientific evaluations of these programs exist. This study aimed to evaluate the effectiveness of an education program developed by the Scottish Society for the Prevention of Cruelty to Animals (SPCA) that included 4 interventions focusing on pets (companion animals), wild animals, farm animals, and general animal rescues. Knowledge, attachment to pets, and attitudes and beliefs about animal minds were assessed at pretest, posttest, and delayed posttest using a questionnaire administered to 1, 217 Scottish children aged 7 to 13 years old. Results showed a significant positive impact of the program on knowledge about animals and the Scottish SPCA for all interventions. The pet and farming interventions significantly impacted children's beliefs about animal minds. There were trends toward improvements in a range of other measures. This study highlights the importance of teaching animal welfare education to children for early prevention of animal cruelty, discusses the need to base this education on theory and research to find effective change, and demonstrates how evidence-based practice can inform future education programs.